2013
DOI: 10.1021/jf3052175
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Assays for the Quantitation of rDNA from Apricot and Other Plant Species in Marzipan

Abstract: Marzipan or marzipan raw paste is a typical German sweet which is consumed directly or is used as an ingredient in the bakery industry/confectionery (e.g., in stollen) and as filling for chocolate candies. Almonds (blanched and pealed) and sugar are the only ingredients for marzipan production according to German food guidelines. Especially for the confectionery industry, the use of persipan, which contains apricot or peach kernels instead of almonds, is preferred due to its stronger aroma. In most of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The analysis of the genome is especially suitable to tackle the biological identity of plant‐ or animal‐based starting materials and can also be used for the differentiation of microorganisms. There are many questions in the food industry like the differentiation of diverse species (e.g., almonds/apricots ) or varieties (e.g., wheat/spelt ; Arriba/CCN51 cocoa ). Due to the high stability of the DNA, processed products which were exposed to moderate temperatures and shear forces can be analyzed too.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the genome is especially suitable to tackle the biological identity of plant‐ or animal‐based starting materials and can also be used for the differentiation of microorganisms. There are many questions in the food industry like the differentiation of diverse species (e.g., almonds/apricots ) or varieties (e.g., wheat/spelt ; Arriba/CCN51 cocoa ). Due to the high stability of the DNA, processed products which were exposed to moderate temperatures and shear forces can be analyzed too.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the modern‐day customers act more emotional than rational by means of consuming, for example, only “regional,” “organic,” “fair trade,” “vegan,” or, on the other hand, animal products solely produced by adequate animal housing. Furthermore, labeling of species or varieties is often used for promotional issues, for example, fine cocoa versus low‐grade cocoa , marzipan versus persipan , or spelt versus wheat .…”
Section: Introductionmentioning
confidence: 99%
“…The ITS regions are widely used to analyze ectomycorrhizal communities of mycorrhizal fungi and fungal species in the field, and it is recommended to be used as the primary fungal barcode [22,23]. Another advantage of the ITS region is the repetitive character resulting in a low detection limit [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, apart from the industrial utilization of apricot kernels in some countries for the production of a marzipan substitute, persipan (Hayta & Alpaslan, 2011), the primary utilization of sweet/debittered apricot seeds recovered from fruit processing plants was indicated as the adulteration of almond kernels and almond oil (Femenia, Rossello, Mulet, & Canellas, 1995). Almond kernels cost twice as much as apricot kernels, thus, apricot seeds become the primary substitute for adulterating marzipan, almond powder, almond oil and even whole almonds in bakery products and confectioneries (Esteki, Farajmand, Kolahderazi, & Simal Gandara, 2017a;Gutfinger & Letan, 1973;Haase, Brüning, Matissek, & Fischer, 2013;Luber, Demmel, Hosken, Busch, & Engel, 2012;Schelm et al, 2016;Van Gansbeke et al, 2018). Marzipan, a product that is exclusively produced from almond paste and sugar, is susceptible to fraud with a cheaper yet similar alternative prepared with apricot kernels, referred to as persipan.…”
Section: Introductionmentioning
confidence: 99%
“…Brüning et al (2011) reported species-specific primers for apricot, peach, pea, bean, lupine, soy, cashew, pistachio, and chickpea to be utilized for the detection of adulteration in marzipan and described the detection of the species-specific amplicons by agarose gel electrophoresis. In consecutive work, the authors described species-specific real-time PCR assays for the detection of the same set of seed species (Haase et al, 2013). Schelm et al (2016) targeted the internal transcribed spacer 1 region of the ribosomal DNA to achieve apricot-specific amplification.…”
Section: Introductionmentioning
confidence: 99%